Intraoperative Seizures in Awake Craniotomy for Perirolandic Glioma Resections That Undergo Cortical Mapping - Eseonu, Chikezie Ikechukwu; Rincon-Torroella, Jordina; Lee, Young M.; ReFaey, Karim; Tripathi, Punita; Quinones-Hinojosa, Alfredo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Perirolandic motor area gliomas present invasive eloquent region tumors within the precentral gyrus that are difficult to resect without causing neurologic deficits.Study Aims This study evaluates the role of awake craniotomy and motor mapping on neurologic outcome and extent of resection (EOR) of tumor in the perirolandic motor region. It also analyzes preoperative risk factors for intraoperative seizures.Methods We evaluated 57 patients who underwent an awake craniotomy for a perirolandic motor area eloquent region glioma. Patients who had positive mapping (PM) or intraoperative identification of motor regions in the cortex using direct cortical stimulation were compared with patients with no positive motor mapping following direct cortical stimulation and negative mapping (NM). Preoperative risks, intraoperative seizures, perioperative outcomes, tumor characteristics, and EOR were also compared. A logistic regression model was used to evaluate the predictors for intraoperative seizures in this patient cohort.Results Overall, 33 patients were in the PM cohort; 24 were in the NM cohort. Our study showed an 8.8% incidence of intraoperative seizures during cortical and subcortical mapping for awake craniotomies in the perirolandic motor area, none of which aborted the case. PM patients had significantly more intraoperative and postoperative seizures (15.5% and 30.3%, respectively) compared with the NM patients (0% and 8.3%, respectively; p = 0.046 and 0.044). New transient postoperative motor deficits were found more often in the PM group (51.5%) versus the NM group (12.5%; p = 0.002). A univariate logistic regression showed that PM (odds ratio [OR]: 1.16; 95% confidence interval [CI], 1.01–1.34; p = 0.035) and preoperative tumor volume (OR: 0.998; 95% CI, 0.996–0.999; p = 0.049) were significant predictors for intraoperative seizures in patients with perirolandic gliomas.Conclusion Awake craniotomies in the perirolandic motor region can be safely performed with a similar incidence of intraoperative seizures as reported for the language cortex. PM in this region may increase the likelihood of perioperative seizures or motor deficits compared with NM. Craniotomies that minimize cortical exposure for perirolandic gliomas that may not localize motor regions can still allow for extensive tumor resection with a good postoperative outcome.
Keywords: awake craniotomy; glioma; eloquent cortex; cortical mapping; seizures